2014
DOI: 10.1186/1471-2407-14-114
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide nanoparticles mediated 131I-hVEGF siRNA inhibits hepatocellular carcinoma tumor growth in nude mice

Abstract: BackgroundHepatocellular carcinoma (HCC) is a primary liver tumor and is the most difficult human malignancy to treat. In this study, we sought to develop an integrative approach in which real-time tumor monitoring, gene therapy, and internal radiotherapy can be performed simultaneously. This was achieved through targeting HCC with superparamagnetic iron oxide nanoparticles (SPIOs) carrying small interfering RNA with radiolabled iodine 131 (131I) against the human vascular endothelial growth factor (hVEGF).Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…[161] Different coatings of magnetite nanoparticles (e.g. [161] Different coatings of magnetite nanoparticles (e.g.…”
Section: Inorganic Nanomaterials As Radioisotope Carriersmentioning
confidence: 99%
“…[161] Different coatings of magnetite nanoparticles (e.g. [161] Different coatings of magnetite nanoparticles (e.g.…”
Section: Inorganic Nanomaterials As Radioisotope Carriersmentioning
confidence: 99%
“…The tumors treated with this complex grew nearly 50% slower in the presence of EMF than those without EMF and the control. The biodistribution analysis showed that the complex stayed in the bloodstream for a short time (t 1/2 = 2.22±0.17 h in the presence of EMF and 3.37±1.17 h in the absence of EMF) [3].…”
Section: Discussionmentioning
confidence: 98%
“…Possible applications include (1) improved delivery of poorly water-soluble drugs, (2) site-directed delivery of drugs towards specific biological and molecular targets, (3) development of innovative diagnostic tools and (4) the combination of therapeutic agents with diagnostic probes [8][9][10][11]. Among all the types of inorganic nanoparticles, gold nanoparticles are the most widely used for drug delivery and other biological applications, due to their non-toxic and biocompatible properties, their size-and shape-controllable synthesis, the ease of surface modification with functional thiolate ligands and their extremely rich and versatile optical properties related to their surface plasmon band [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle drug delivery systems maximize the permeability and retention of drugs in solid tumors, and thus can reduce systemic toxicity and reverse drug resistance mechanisms by improving availability and activity at tumor sites [22,23]. During the last two decades, intensive research has focused on various nano-based approaches, but few types of nanoparticles have been utilized for DTX delivery [11,21]. Nanoparticle DTX delivery systems should have the following properties: (1) good solubility under physiological conditions, (2) good stability until the drug arrives at the target cancer cells, (3) selectivity and efficiency in targeting cancer cells, (4) slow release in cancer cells and (5) minimal side effects toward normal cells.…”
Section: Discussionmentioning
confidence: 99%